New towns in Peninsular Malaysia: planning and development / Dasimah Omar - Omar, Dasimah (2004)
The planning and development of new towns had been based on various planning objectives and has met different levels of success. The idea of the garden city movements was found to be an important approach in city planning and in creating the urban pattern. The basic principles of new town development to be considered included limiting the size of new towns in terms of scale of population, provision of green belts and creating a well connected system of cities. Perhaps the most significant aspect of new town development is the policy to seek an economic balance between housing, facilities, industrial and commercial development. The original idea in Howard's 'garden city' concept has been modified for various reasons and to meet wider policy aims. New towns were found to be significant for another important reason: as the element for decentralization of congested city centres. There is a strong need for an integrated national policy for new town development in Malaysia intended to coordinate and regulate large schemes and minimise competitive urban growth. There is no national policy yet to balance spatial development between states. If the planning and development of new towns is to be effective, a package of policy agenda, target and plan formulation and a co-ordinated scheme of implementation will become necessary condition.